Imported Hellenistic Stamped Amphora Handles and Fragments from the North Sinai Survey - Ariel, Donald T. (Journal of Hellenistic Pottery and Material Culture, 2017)
The 1972–1978 archaeological survey of North Sinai (›The North Sinai Expedition‹) encompassed an area of ca 2000 square km, which included the ›Ways-of-Horus‹, part of the all-important long-distance trade route, the ›Via Maris‹. Consequently the recovery of quantities of fragments of transport amphoras was to be expected. This is especially true of the major coastal stations known from ancient written sources.